2017
DOI: 10.3389/fnmol.2017.00306
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Cigarette Smoke Exposure Worsens Neurological Outcomes in Adolescent Offspring with Hypoxic-Ischemic Injury

Abstract: Hypoxic-ischemic (HI) encephalopathy occurs in approximately 6 per 1000 term newborns leading to devastating neurological consequences, such as cerebral palsy and seizures. Maternal smoking is one of the prominent risk factors contributing to HI injury. Mitochondrial integrity plays a critical role in neural injury and repair during HI. We previously showed that maternal cigarette smoke exposure (SE) can reduce brain mitochondrial fission and autophagosome markers in male offspring. This was accompanied by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 79 publications
4
44
1
Order By: Relevance
“…In the foot fault test, we have found that prenatal e‐Cig exposure impairs motor coordination in both sham and HI adolescent offspring. Chan et al showed that prenatal TS exposure impairs limb coordination in adolescent male offspring with HI brain injury which supports our findings (Chan, Saad, Machaalani, et al, ). Our results indicate that maternal e‐Cig exposure combined with HI brain injury could be a significant insult to affect offspring cognitive and motor functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the foot fault test, we have found that prenatal e‐Cig exposure impairs motor coordination in both sham and HI adolescent offspring. Chan et al showed that prenatal TS exposure impairs limb coordination in adolescent male offspring with HI brain injury which supports our findings (Chan, Saad, Machaalani, et al, ). Our results indicate that maternal e‐Cig exposure combined with HI brain injury could be a significant insult to affect offspring cognitive and motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…TS has been shown to increase the risk of fetal hypoxia (Habek, Habek, Ivanisevic, & Djelmis, ) and reduce the oxygen carrying capacity of both fetal and maternal red blood cells (Bureau et al, ). Perinatal nicotine and TS exposure have been demonstrated as a significant insult which can also exacerbate the sensitivity of neonatal brain to HI injury (Chan, Saad, Machaalani, et al, ; Froen, Amerio, Stray‐Pedersen, & Saugstad, ; Li, Xiao, et al, ). During neonatal HI brain injury, alterations of brain glucose and energy metabolism occur (Vannucci, Seaman, & Vannucci, ), which can play a crucial role in the short‐ and long‐term outcome of this injury in animals.…”
Section: Introductionmentioning
confidence: 99%
“…ROS will firstly damage the mitochondria and DNA. Maternal SE is indeed linked to reduced mitochondrial density in multiple brain regions in the male offspring …”
Section: Potential Cellular Mechanismsmentioning
confidence: 98%
“…The outcomes of HI are a diminished exchange of oxygen and carbon dioxide, and severe lactic acidosis, increasing the risk of cerebral palsy after birth . Studies in rodents using both maternal nicotine administration and SE showed an increase in the vulnerability of the neonatal brain to HI encephalopathy, leading to more severe neurological functional loss in the offspring from nicotine treated/SE dams than those from the control dams, including the risk of cerebral palsy . Indeed, the risk of cerebral palsy is high in individuals whose mothers are heavy smokers (≥10 cigarettes/day) .…”
Section: Maternal Cigarette Smoking and Neurocognitive Outcomesmentioning
confidence: 99%
See 1 more Smart Citation